The Political Poetics of Contrastive Identifications: Scripting Ongoing Events Through Master/Counter Positioning in Populist Political Speech - Rautajoki, Hanna (Narrative Works, 2024)
The article reports an empirical inquiry into the rhetorical use of master/counter juxtapositions in narrating an ongoing scene of political action. Drawing on the studies of institutional interaction, it investigates the institutional setting of public political speeches, focusing on the empirical example of Donald Trump’s public speech in the rally after the election results and just before the violent invasion of the United States Capitol on January 6, 2021. My research approaches master/counter positioning as a multilayered relational constellation of identifications mobilized in the telling and deployed strategically for specific institutional purposes. I am interested in counter-narratives as interpretative discursive frames superimposed on surrounding socio-material circumstances to refute an alternative (pre-existing and prevailing) interpretation of reality. My take on the concept as a multifaceted rhetorical resource subsumes the aspects of an act of contestation, a breach of cultural orders, and a mission towards emancipation, albeit in a slightly modified version of the conventionalized definitions. In the context of political interaction, that is, in institutional activities connected to ongoing processes in policy-making and governance, counter-narratives are world-breaking but they are also world-making in a decidedly concrete consequential manner, firstly, by building on institutional continuities, virtues, and legitimacies, and secondly, by addressing recipients as co-actors, projecting identifications on them and expecting them to assume a role in the political participation field at hand. Applying tools from small story research, membership categorization analysis, epistemic governance and narrative positioning analysis, I explore the purposeful evocation of contrastive storylines in political rhetoric. The article aims to shed light on the argumentative use of counter-narratives in a political line of action.